Análisis del tratamiento contable y financiero que se aplica a los productos financieros derivados (2013)
The derivates are financial tools used to edge or reduce some risks that happen in an inherently way when you are tradingforex or stocks. The financial sector entities use them to speculate on the value of the assets traded but ensuring through pacts, as previously referred to in a contract, a price for the exchange of these. There are different contracts, each of them with characteristics that make them different; thanks to this you can analyze which of them will accommodate conveniences and circumstances presented in the moments that pass the market. In Chapter XVIII of External Circular 014 of 1998, issued by the superintendent of banks, it is given the pattern to account the obligations and rights that are in these contracts at the sign them, by causing the differences between the market price and the price of contract and to make it effective.